2021
DOI: 10.1001/jamanetworkopen.2021.16233
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Follow-up Testing Recommendations in US Veterans Screened for Lung Cancer, 2015-2019

Abstract: IMPORTANCE Lung cancer screening (LCS) can reduce lung cancer mortality with close follow-up and adherence to management recommendations. Little is known about factors associated with adherence to LCS in real-world practice, with data limited to case series from selected LCS programs. OBJECTIVE To analyze adherence to follow-up based on standardized follow-up recommendations in a national cohort and to identify factors associated with delayed or absent follow-up. DESIGN, SETTING, AND PARTICIPANTS This retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 66 publications
(103 reference statements)
2
37
1
Order By: Relevance
“…This study is consistent with prior studies showing that Black individuals are less likely to receive an initial LCS, and when they do undergo LCS, they are about 30% less likely to receive the recommended follow-up ( 2 4 ). These are highly concerning findings as Black men have the highest lung cancer incidence and mortality from lung cancer of any demographic group ( 5 ), and Black populations may derive greater relative mortality benefits from screening ( 6 ).…”
supporting
confidence: 91%
“…This study is consistent with prior studies showing that Black individuals are less likely to receive an initial LCS, and when they do undergo LCS, they are about 30% less likely to receive the recommended follow-up ( 2 4 ). These are highly concerning findings as Black men have the highest lung cancer incidence and mortality from lung cancer of any demographic group ( 5 ), and Black populations may derive greater relative mortality benefits from screening ( 6 ).…”
supporting
confidence: 91%
“…The programs reached different demographic segments of the population, potentially providing a means of overcoming the looming problem of access disparity to lung cancer screening, which threatens to widen racial, sex, and socioeconomic and geographic disparities in lung cancer mortality. [11][12][13][14][15][35][36][37][38][39][40][41][42] Despite evidence from two large randomized clinical trials that lung cancer screening saves lives, adoption has been slow, difficult, and complex, even in the United States where social policy moved in 2015 to provide payment for annual LDCT screening as part of standard health care coverage. 6,43 Barriers to implementation include the need for infrastructure for recruiting candidates who meet eligibility criteria for screening and conducting the mandated shared decision making and tobacco cessation counseling services required before the LDCT screening test can be performed.…”
Section: Characteristics Of Patients Diagnosed With Cancermentioning
confidence: 99%
“… 33 , 34 , 35 However, prior work has shown lower LCS rates among racial and ethnic minority groups and those with lower socioeconomic status, 7 , 8 and we previously found lower adherence to recommended follow-up after initiating LCS among Black veterans and those with lower income. 18 The current study adds to this literature by suggesting that disparities in LCS uptake and adherence may not be associated with screening hesitancy at the patient level but rather with structural barriers preventing receipt of equitable care. Our study found that overall, veterans with better access and connection to VHA care, as indicated by more VHA outpatient visits in the prior year, were more likely to accept LCS.…”
Section: Discussionmentioning
confidence: 74%
“…We selected clinically relevant covariables a priori based on prior studies of factors related to uptake of or adherence to LCS, including self-reported race and ethnicity to explore potential disparities in declining LCS. 18 , 19 , 20 , 21 , 22 , 23 For each veteran, we extracted data from the VA Corporate Data Warehouse on demographic characteristics and VA priority status (the VA’s system to determine co-payments). We used a veteran’s residential zip code to estimate median income, and we assessed urbanization using the US Census Bureau Rural-Urban Commuting Area codes.…”
Section: Methodsmentioning
confidence: 99%